ASSESSMENT OF COMPLIANCE WITH SUSTAINABILITY PRACTICES IN LINE WITH A3P GUIDELINES, BASED ON THE PERCEPTIONS OF CDSA/UFCG EMPLOYEES (Editora Impacto Científico, 2025)
The present study sought to examine the perceptions of CDSA/UFCG staff concerning the predictability and adoption of actions or initiatives aimed at fostering the development of sustainability practices consistent with the guidelines of the A3P. The administration of the questionnaire yielded a sample of 91 participants (faculty and administrative staff), representing approximately 64% of the total population, thereby ensuring a confidence level exceeding 90%. Overall, the findings indicate that the perception of CDSA/UFCG staff regarding the adoption and implementation of sustainability practices aligned with the A3P guidelines reflects a process that is both partial and gradual. With respect to adherence to and implementation of such aligned practices, it is reasonable to observe that perceptions vary according to each specific axis established by the A3P.DOI: https://doi.org/10.56238/edimpacto2025.064-034